(untitled) (Annals of Medical Research, 2023)
Aim: Colon adenocarcinomas are the most common gastrointestinal tract malignancy and constitute one of the leading causes of mortality and morbidity worldwide. STAT3 is a transcription factor activated by many cytokines and growth factors and plays a crucial role in cell survival, proliferation, and differentiation. In this research, we aimed to elucidate the molecular properties of colon tumors. Materials and Methods: A total of 196 patients with metastatic colon tumors whose samples were analyzed for KRAS, NRAS, and BRAF between 2016 and 2022 have been investigated in this retrospective study. The samples were analyzed via polymerase chain reaction (PCR) at our institution. On the formalin-fixed, paraffin-embedded tissue blocks, immunohistochemistry was performed to determine STAT3 expression. Immunohistochemical staining with a fully automated assay was performed on 3-4 μm-thick slices based on manufacturer’s instructions. Phospho-STAT3 (Tyr705) [RM261] Conc. 0.1mL (1:1000-10000) antibodies were used on the Ventana® Benchmark XT (Ventana-Roche Diagnostics, Meylan, France). All the slides were examined by a pathologist. STAT3 expression was scored between 0 and 3 points due to staining intensity. No staining was considered as 0, light staining as 1, moderate staining as 2, and strong staining as 3 points. Results: A total of 196 patients, 79 (40.3%) female and 117 (59.7%) male, were included in the evaluation within the scope of the study. There was no significant difference between STAT3 staining intensities in terms of demographic characteristics. On the contrary, there was a statistically significant relationship regarding tumor grades (p<0.05). KRAS mutation was found in 40.8% of the patients (n=80), NRAS mutation was found in 2% (n=4), and BRAF mutation was found in 4.1% (n=8). It was determined that there was a statistically significant relationship between KRAS and STAT3 grades of mutations (p<0.05). It is seen that KRAS positivity increases as the STAT3 staining intensity of the patients’ increases. There was no statistically significant correlation between other mutation results and STAT3 grades. Conclusion: In light of the findings obtained from our study and previous literature, it has been determined that routine STAT3 gene screening is a necessity before the treatment is determined.